Community Based Tourism Management at Geger Beach a Tourist Destination in Nusa Dua Bali - Marina, Marina; Kanom, Kanom; Sumardani, Rizki; Negara, I Made Weda Satia (Jurnal Manajemen Pelayanan Hotel, 2024)
The purpose of this study was to identify the management of Geger Beach as a Tourism Destination in Nusa Dua, Bali based on local communities and to determine the economic impact of local communities on the management of Geger Beach Tourism Destination in Nusa Dua, Bali. This research uses qualitative research, the research location is on the beach of Geger Nusa Dua Bali. The data sources in the study are primary data sources and secondary data as well as research instruments such as stationery, cellphones, interview guidelines and tools that support this research informants in the study were 1) the management of Geger Beach, 2) local local communities 3) tourists visiting Geger Beach, The number of informants in this study was 10, and the method of collecting data in this study using observation, interviews, documentation, and literature study. The method of data analysis in this study through several stages, including data reduction, data presentation, and conclusion drawing involves three main steps to process research data. The results survey that Geger Beach Management in Nusa Dua is based on local communities with a focus on community participation development and management of tourist facilities and services responsibly, to balance economic benefits and cultural preservation. This participation includes resource management, cultural promotion, and the organisation of tourist activities. The economic impact is significant for local communities, with increased income through tourism services, culinary and craft businesses, and new employment opportunities. In addition, this participation encourages communities to be active in the conservation and development of tourist destinations.